Measuring ministers' attitudes toward juvenile delinquency - Alberts, William Edward (1961)
Abstract: p. 266-268. Autobiography: p. 269-270. Bibliography: p. 257-260. Thesis (Ph.D.)—Boston University N.B.: Pages 197, 222, and 261 appear to be missing in all copies. We believe that these were all misnumbered by the author, and that no actual information is missing.This is a psychological study of Protestant ministers' attitudes toward juvenile delinquency, and of their theological beliefs. The study has been guided by two hypotheses. The first hypothesis proposed that an interrelationship existed between a minister's attitudes regarding the causes and treatment of the different delinquencies and the degree of authoritarian or supportive tendencies in his personality. The second hypothesis assumed that an interrelationship existed between what a minister did in regard to juvenile offenders and his underlying attitudes toward causation and treatment. The survey of the ministers' theological beliefs focused on the possibility of an interrelationship between their beliefs and their attitudes toward delinquent behavior. Two methods were employed to collect data and test the hypotheses: a Juvenile Delinquency Attitude (JDA) scale was constructed and administered to ninety-two ministers; then forty of the seventy-four respondents completing the scale were interviewed. The questionnaire also contained the Fascism (F) scale, which measures implicit antidemocratic tendencies in the personality, and the Traditional Family Ideology (TFI) scale, which measures attitudes toward family structure and functioning on a democratic-autocratic continuum. Following are the findings. (1) The contrasting responses of the high (authoritarian) and low (supportive) scorers to the items of the JDA scale demonstrated the discriminatory power of the items and the interrelatedness of the authoritarian variables of the scale. (2) The test of reliability indicated a correlation of .95 of the JDA scale test-retest and of .92 from the test score correlations. These correlations show a high degree of consistency between the ministers' responses in the first and second administrations of the scale. (3) The correlation between the JDA and F scales was .831, between the JDA and TFI scales .817, and the correlation between the F and TFI scales was .774. These high correlations supported the hypothesis that a minister's internal frame of reference, i.e., his deep-rooted emotional dispositions, determined to a great extent, the nature of his attitudes toward the causes and treatment of juvenile delinquency. (4) The data obtained in the interviews with the high and low scorers supplemented their respective scores on the JDA scale. High scorers viewed causation on a symptomatic level, communicated an authoritarian philospphy of treatment, expressed messianic concepts regarding the role of the church in treatment, and indicated limited awareness and utilization of community resources. Conversely, low scorers revealed a comprehensive understanding of delinquent motivation, a supportive philosophy of treatment, an interpersonal view of the church as a rehabilitative resource, and a high awareness and utilization of community resources. In addition the high scorers tended to be authoritarian and low scorers supportive in their handling of youth offenders. This finding substantiated the hypothesis that a minister's treatment of youth offenders was related to his attitudes toward juvenile delinquency. (5) The measurement of the respondents' theological beliefs showed no significant correlation between their beliefs and their attitudes toward juvenile delinquency. The data revealed that both high and low scorers identified with similar theological positions. This finding indicated that religious beliefs can be reinterpreted to accommodate authoritarian ar supportive tendencies. The finding was supported by the significant scores of the high scorers on the messianic sentimentality variable of the JDA scale. While they agreed with the apparently supportive items of the scale, their agreement with a large majority of contradictory authoritarian items suggested that they may have intellectually accepted the conventional view of supportive pastoral care and still rationalized conflicting attitudes and dispositions toward juvenile offenders and offenses. On the basis of these data, therefore, it was concluded that a minister's deep-lying emotional dispositions, more than his abstract theological beliefs, generally determine the nature, extent, and effectiveness of his approach to juvenile delinquency. [TRUNCATED